Prevalência de coccidiose e correlação com a saúde intestinal de frangos de corte em agroindústrias brasileiras entre os anos de 2012 a 2014 - Gazoni, Fabio Luis (2015)
Coccidiosis is a disease caused by protozoa of the genus Eimeria ssp. These protozoa are intracellular parasites of enterocytes that rupture the host cell, causing damage to the intestinal mucosa. The lesions caused by Eimeria reduce nutrient uptake by broilers, affecting their productivity gain, and also represent a portal of entry for other enteropathogens. The aim of this study was to assess the correlation between lesions caused by Eimeria and the prevalence of coccidiosis and other gastrointestinal disorders among broilers reared in Brazil from 2012 to 2014. Intestinal health was evaluated at 82 poultry houses in Brazil, totaling 5,528 birds aged 12 to 40 days. The rearing period was divided into two phases: phase 1 (12 to 21 days) and phase 2 (22 to 40 days). The broilers, at least three per shed, were collected from three different sites. The following gastrointestinal aspects were analyzed in the present study: presence of cell desquamation, excess fluid, excess mucus, ingestion of contaminated litter, thickened intestinal walls, thin intestinal walls, movement of food bolus, abnormal intestinal tonus, Turkish towel appearance, verminosis, and necrotic enteritis. The classification of the scores for gross lesions caused by Eimeria acervulina, Eimeria maxima, and Eimeria tenella followed the method proposed by Johnson & Reid, [8] and the oocyst count of E. maxima (E. maxima micro) in the mucosa was performed under a light microscope at 100X magnification. The statistical analysis of the Pearson correlation coefficient was carried out by the SAS 9.3 software program [16], using a 95% confidence interval. The results of this study revealed that E. acervulina was the most prevalent (mean of 13.5%) species in both rearing stages. Also, there was a positive correlation with thin intestinal walls and abnormal intestinal tonus in phases 1 and 2, as well as a positive correlation with ingestion of contaminated litter in phase 2. The second highest prevalence was that of E. maxima (mean of 6.75%), with a positive correlation with excess mucus, thickened and thin intestinal walls in phase 1, and a positive correlation with cell desquamation, excess fluid, and Turkish towel appearance in phase 2. E. tenella yielded the lowest prevalence rates (mean of 4.35) among the analyzed Eimeria species, showing a positive correlation with excess fluid in phases 1 and 2 and with thickened intestinal walls and lesions caused by E. maxima in phase 2. The microscopic analysis demonstrated that E. maxima was found in 18% of mucosal scrapings in phase 1, which accounts for a subclinical coccidiosis rate of 282.98% compared with clinical coccidiosis. A positive correlation was observed for E. maxima micro between thickened intestinal walls and lesions caused by E. maxima. E. maxima was detected in mucosal scrapings of 29.6% of the broilers in phase 2, accounting for a subclinical coccidiosis rate of 236.37% compared with clinical coccidiosis. E. maxima micro revealed a positive correlation with excess fluid, necrotic enteritis, E. acervulina, E. maxima, and E. tenella in phase 2. The comparison between the rearing periods showed that subclinical coccidiosis affected 64.45% more broilers in phase 2 than in phase 1. In the gross analysis, E. acervulina was the most prevalent species in both rearing periods. A lesion score equal to 1 was the most frequent among all Eimeria species. Subclinical coccidiosis affected a significant number of broilers in the analyzed Brazilian flocks, and was correlated with several factors that reduce intestinal health. It may be concluded that monitoring is of utmost importance to find out the status of intestinal health of poultry. The microscopic detection of E. maxima (mean of 23.8%) is correlated with factors that negatively affect intestinal health.